Knowledge, attitude and practice on personal financial management among undergraduate students - Aini Wahida Suwaimi
Financial management play an important role in student's life which is to ensure that financial problems will not interfere in student learning processes. Without proper financial management, it will cause a lot of problems in handling the financial aid. This problem is not a new issue among universities students. Thus, the main objective of this study is to determine the factors that will influence the financial management practice among students. More specifically this study aimed to determine the correlation between financial management knowledge and attitude towards financial management practice among students in higher education institution. The study was based on samples gathered from undergraduate students in Universiti Sultan Zainal Abidin (UniSZA), using a self-administered questionnaire. Of the total 400 questionnaires distributed, 385 returned the questionnaire, giving a response rate of 96%. IBM SPSS Statistic 20 approach was used to analyze the data and to test the hypotheses. The results suggested that the financial management attitude give impact towards financial management practice. However, the impact of financial management knowledge towards financial management practice was not significant. Therefore, in this research found that overall of the undergraduate students in UniSZA has positive financial management attitude, but low in both financial management knowledge and financial management practice. This study highlights on the factors that influence financial management practice among the undergraduate students in UniSZA as well as provides some suggestions regarding the future research. This research sets preparation for the future research and signals for financial education program at the pre-university and university level, to help students in their personal financial management.